2001
DOI: 10.1054/bjoc.2000.1599
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic advantage of preoperative intratumoral injection of OK-432 for gastric cancer patients

Abstract: SummaryTo investigate, by a multi-institutional randomized trial, the prognostic significance of the augmentation of tumour-infiltrating lymphocytes (TILs) by preoperative intratumoral injection of OK-432 (OK-432 it), a bacterial biological response modifier, in patients with gastric cancer. The 10-year survival and disease-free survival were examined and analysis of the factors showing survival benefit was performed. 370 patients who had undergone curative resection of gastric cancer were enrolled in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…This strategy permits higher and more frequent doses of an anticancer drug for use in tumor therapy. 44 Injection of As 2 O 3 into transplanted esophageal carcinomas resulted in a higher concentration of As 2 O 3 in the tumors than in other organs, and efficiently suppressed tumor growth without systemic side-effects. 10 The strategy adopted in our study is a further advance in that it targets not only primary HCCs, but also targets secondary distant tumors due to the antitumor systemic immunity that develops.…”
Section: Discussionmentioning
confidence: 98%
“…This strategy permits higher and more frequent doses of an anticancer drug for use in tumor therapy. 44 Injection of As 2 O 3 into transplanted esophageal carcinomas resulted in a higher concentration of As 2 O 3 in the tumors than in other organs, and efficiently suppressed tumor growth without systemic side-effects. 10 The strategy adopted in our study is a further advance in that it targets not only primary HCCs, but also targets secondary distant tumors due to the antitumor systemic immunity that develops.…”
Section: Discussionmentioning
confidence: 98%
“…In a clinical trial with 395 patients (Tanaka et al 1994), a signi® cant improvement in ® ve-year survival was demonstrated for intratumoral OK-432 for patients with stage III disease (48 % survival with intratumoral OK-432 vs 28% for controls). Quite recently, results were presented for a 10-year clinical study of intratumoral immunotherapy with OK-432 in 370 gastric cancer patients (Gochi et al 2001). In the intratumoral study group, patients received endoscopically-injected intratumoral OK-432 one to two weeks before surgery followed by postoperative adjuvant therapy with one intravenous dose of mitomycin plus oral tegafur and intradermal OK-432.…”
Section: Bacterial and Other Immunomodulatorsmentioning
confidence: 99%
“…Adjuvant immunotherapy is expected to exert a synergistic effect with surgical resection. For example: OK-432, a streptococcal preparation, which is one of the most commonly used non-specific enhancer of immune system, demonstrated marginal improvement in survival for patients with stage III gastric cancer [120]. Administration of OK-432 has been reported to induce the release of various cytokines, such as TNF-α, INF-β, IL-8, IL-12, etc., and has also been shown to enhance cytotoxicity against autologous cells.…”
Section: Gastric Cancer Immunotherapymentioning
confidence: 99%